The thistle and the drone : how America's war on terror became a global war on tribal Islam - Ahmed, Akbar S. (Brookings Institution Press, 2013)
In the wake of the 9/11 attacks, the United States declared war on terrorism. Morethan ten years later, the results are decidedly mixed. Here world-renowned author, diplomat, and scholar Akbar Ahmed reveals an important yet largely ignored result ofthis war: in many nations it has exacerbated the already broken relationship between central governments and the largely rural Muslim tribal societies on the peripheries of both Muslim and non-Muslim nations. The center and the periphery are engaged in a mutually destructive civil war across the globe, a conflict that has been intensified by the w.